Toxicological effects of veterinary medicinal products in humans; VOL.1 - Woodward, Kevin N (Royal Society of Chemistry, 2013)
Toxicological Effects of Veterinary Medicinal Products in Humans is the first definitive guide to discuss the adverse effects of veterinary medicinal products in humans.